Analysis of Grammatical Cohesion in the Reading Texts of the “English for Nusantara” Ninth Grade Textbook - Tiara Andhini; Safnil Arsyad (Universitas Negeri Gorontalo, 2026)
This study examines the use of grammatical cohesive devices in the reading texts of the English for Nusantara textbook for ninth-grade. This study employed a descriptive qualitative approach, and analyzed 14 reading texts to identify four types of grammatical cohesion: reference, substitution, ellipsis, and conjunction, based on Halliday and Hasan’s framework. The findings reveal that a total of 694 instances of grammatical cohesion were identified in the textbook. Reference emerged as the most dominant cohesive device with 552 occurrences, followed by conjunctions with 132 occurrences. Ellipsis appeared only 6 times, while substitution only 4 times. These findings show that the textbook relies heavily on explicit cohesive devices, particularly reference and conjunction, to maintain textual coherence. And it suggests that the English for Nusantara textbook effectively supports students’ reading comprehension by providing clear grammatical links between sentences, although the limited use of substitution and ellipsis indicates a restricted variety of cohesive devices.